Generation and storage of double slow light pulses in a solid - 范云飞 王海华 王荣 张晓军 康智慧 吴金辉 张汉壮 高锦岳 (Chinese physics B, 2012)
We experimentally study the generation and storage of double slow light pulses in a pr^3＋：Y2SiO5 crystal. Under electromagnetically induced transparency, a single signal pulse is stored in the spin coherence of the crystal. By simultaneously switching on two control fields to recall the stored information, the spin coherence is converted into two slow light pulses with distinct frequencies. Furthermore, the storage and controlled retrieval of double slow light pulses are obtained by manipulating the control fields. This study of double slow light pulses may have practical applications in information processing and all-optical networks.